Advances in Fine and Coarse Particle Flotation (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
Flotation works very well for particles that are typically in the range 20 to 150 µmin diameter, for base metal ores. In this range, it is possible to get quite high recoveries in conventional flotation machines. Outside this range, the recoveries decline progressively, whether it be with the very fine or the coarse end of the size spectrum. In this paper, the reasons for the drop-off in recovery are briefly reviewed, together with strategies for future work. Recent progress in the author's laboratory will be described. These include the Concorde Cell, which takes advantage of the high dissipation rates in the shock wave created when a gas-liquid mixture reaches supersonic velocities. The environment thus created is very beneficial for the flotation of ultrafines. For coarse particles, the reasons for the drop-off in recovery can be related to the highly turbulent nature of the pulp in a conventional flotation cell. To improve recovery, it is necessary to find a way of bringing particles and bubbles into contact in a quiescent environment. A new process for coarse particle flotation will be described, in which a fluidized bed is created in the flotation cell. The flow conditions are very gentle, and the high solids concentration leads to rapid rates of capture of the particles. Experimental results are presented. It is apparent that the maximum floatable size for coal and minerals can be increased by a factor often over the limits found in current practice. Advances